Hypotheses about Unknowing: How Writing Poetry Can Aid Clinical Craft - Bolin, Chris (Ars Medica, 2014)
The language of the medical profession involves, of course, the nomenclature of the body—and it involves the nomenclature of the undoing of the body. It is a language as equally steeped in presence as in absence. Like poetry, it is a language that finds evidence for itself—and, like poetry, it finds much of its evidence in the “data of the moment."